HUMAN MOTRICITYAND QUALITYOF LIFE (Fiep Bulletin - online, 2012)
There is a consensus on the benefits that physical exercise can provide for quality of life, however, whenanalyzing the complexity of the concept of quality of life we realize that, for effectiveness of the Physical EducationProfessional, it's needed a strong knowledge, not only about the biological aspects of the physical exercise, but allhuman being's complexity and then to contribute not for just the health extent, but for all the spheres of the qualityof life. The Science of Human Kinetics takes the professional to worry about, besides technical questions, thedevelopment of a wide vision of the world where we live and of the wanted one, as well about the man and thesociety so they can be able to act in an efficient way in the health and quality of life.